(untitled) (Journal of Philosophy Culture and Political Science, 2018)
Search of answers to questions on life meaning is impossible without the reference to history of philosophy where we shall find set of "advice", “opinions and doubts” of thinkers, who aspire to protect people from spiritual barbarity, to open “reasonable, kind, eternal” in each person, to warn that it is necessary to care not only of means of life, but also about the purposes of life.